Enfermagem e gestantes de alto risco hospitalizadas : desafios para integralidade do cuidado - Souza, Bruna Felisberto de (2017)
Innumerous specificities of the pregnancy-puerperal cycle lead and claim for health practices aimed at qualified listening, empathy and acceptance, especially in the face of the understanding of this phenomenon in its physical, psychic and social transformations. However, the current health obstetrical model is supported by the biomedical view, which disrespects and ignores women’s right to health, from a perspective of little involvement in their care, limiting access and information. This reality infers that women have a submissive role in the system, especially in situations of greater vulnerability, as in the case of gestating and giving birth in a condition of high risk. This qualitative and field study aimed at characterizing and discussing the nursing care practice of a maternity nursing team to hospitalized high risk pregnant women. We used Integrality and Care in health practices as theoretical conceptual basis and as a methodological reference Content Analysis, in its thematic modality. The data were collected in a municipality in the interior of the state of São Paulo, through non-participant observation of nursing care to high-risk pregnant women followed by an individual and open interview with six nurses, four nursing technicians and two nursing assistants, totaling twelve participants, responsible for direct care to hospitalized pregnant women at risk. The analysis of empirical data allowed us to identify that the care practice of hospitalized high risk pregnant women is anchored in three processes, portrayed by the thematic categories “Emotional welcome”, “Information support” and “Evaluation and monitoring of gestational risk”. In the first thematic category, we noted efforts to provide a practice guided by empathy and acceptance, with recognition of these axes as aspects that base the humanization of care. Another integrating front of the practice of care is the provision of information, supported by the recognition of insufficiency and even the lack of information to women about the risk situation. However, they prioritize instrumental practice as an assistance core, referencing the nurse in support of this practice. It is concluded that, in fact, nursing care practice is central in instrumental actions and support to the physician. However, in its intentions it denotes centrality in the women's desire for emotional and informational reception, when they invest in achieving good interpersonal relationships with pregnant women. Relations between these issues are poorly interconnected, with emphasis on technical successes, with weaknesses in terms of practical successes, which does not allow them to be classified as integral. Attitudinal and structural changes are thus necessary, with attention to the humanistic and integrality precepts and, above all, focused on the practical success of the actions.